2021
DOI: 10.2147/jmdh.s297503
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of Healthcare Staff Working During the COVID-19 Crisis: Their Working Hours as a Boundary Condition

Abstract: Purpose: Healthcare staff operate at the forefront of the fight against COVID-19 and hence face enormous physical and mental pressures. We aim to investigate healthcare staff's mental health issues and the associated predictors during the COVID-19 pandemic. Specifically, this paper aims to identify some unique predictors of healthcare staff's mental health issues in Iran, the second country after China to experience a major COVID-19 crisis. Methods: An online survey of 280 healthcare staff in all 31 provinces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Among the mental health symptoms examined, distress and depression generally had the highest prevalence rates. Our findings suggest that practitioners need to pay more attention to distress and depression of various populations under the COVID-19 pandemic [ 76 - 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the mental health symptoms examined, distress and depression generally had the highest prevalence rates. Our findings suggest that practitioners need to pay more attention to distress and depression of various populations under the COVID-19 pandemic [ 76 - 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, this study has interviewed young subjects in a small age range who had poor health risks related to COVID-19 infection ( Bagus et al., 2021 ). Compared with children and old people, the pandemic-related psychological distress for young subjects was limited ( Horiuchi et al., 2020 ; Gong et al., 2021 ). Then, the extent of the lockdown ( Bell et al., 2021 ), pre-existing depressive disorders ( Yamamoto et al., 2020 ), and food insecurity ( Serafini et al., 2021 ) have been proved to significantly impact the PD prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Access to PPE predicted better physical health, job satisfaction, and lower distress in healthcare workers. Those unsure about their COVID-19 infection status were more likely to experience distress, anxiety, and depression symptoms and had lower job satisfaction ( 18 , 44 ). Findings from Peru indicated that healthcare workers with a lower education level were more anxious, and younger healthcare workers and those in the private sector were more susceptible to job turnover ( 45 ).…”
Section: Discussionmentioning
confidence: 99%